The effectiveness of pairs trading strategy in light of market volatility - Domingues, Nuno Ramos Da Fonseca (2021)
This paper show Pairs trading strategies are proved to be efficient for the European stock market between Jan 2010 to April 2021in light of different volatility regimes. An association with the strategies returns and volatility is established, and results show that increasing levels of volatility lead to significant higher gains caused by a widening of the spreads while decreasing regimes of volatility lead to high trading frequencies. For situations where we focus on this two different regimes, the enhanced strategy outperforms the basic pairs trading strategy on a risk-reward basis with higher sharpe ratios.